2020
DOI: 10.1111/jcmm.15752
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of sortilin is associated with 5‐FU resistance and poor prognosis in colorectal cancer

Abstract: Worldwide, colorectal cancer (CRC) is the third most commonly occurring cancer and the second leading causes of cancer-related deaths. 1,2 Systemic 5-fluorouracil (5-FU) has been used for decades, and remains the first-line molecule used in CRC chemotherapy. 3 It is currently used in combination with other antitumour agents such as irinotecan, oxaliplatin, folinic acid, and also targeted therapies. Unfortunately, 5-FU resistance renders combined chemotherapies mostly ineffective 4,5 and leads to relapse and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…According to earlier studies, patients with higher or positive SORT1 expression exhibited worse prognosis and advanced tumor progression in breast cancer, 14 B acute lymphoblastic leukemia, 27 neuroendocrine tumors 16 and colorectal cancer, 13 suggesting that SORT1 could be a biomarker to predict the survival time of patients with malignant tumors. In this research, after data mining based on the TCGA-LIHC dataset, it was uncovered that SORT1 expression was substantially As demonstrated in previous studies, SORT1 inhibition could slow down tumor growth and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to earlier studies, patients with higher or positive SORT1 expression exhibited worse prognosis and advanced tumor progression in breast cancer, 14 B acute lymphoblastic leukemia, 27 neuroendocrine tumors 16 and colorectal cancer, 13 suggesting that SORT1 could be a biomarker to predict the survival time of patients with malignant tumors. In this research, after data mining based on the TCGA-LIHC dataset, it was uncovered that SORT1 expression was substantially As demonstrated in previous studies, SORT1 inhibition could slow down tumor growth and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…12 As a multifaceted protein, SORT1 assumes cancerogenic or anticancer roles in human cancers depending on the origin of the tumors. 13 For instance, SORT1 silencing retards breast cancer progression and lung metastases. 14 Sortilin 1 knockdown suppresses gastric cancer cell proliferation, invasion, and migration.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we screened HCC genes from GEO and TCGA data and identi ed the di erentially expressed molecule Sort1 from the di erential genes. Previous studies have shown that Sort1 acts as an oncogene that is linked with poor prognosis in gastric [24], prostate [25], and colorectal cancers [26], but there is no relevant study on a similar mechanism in HCC. We veri ed the ability of reduced Sort1 expression in inhibiting HCC proliferation and invasion, with the ndings expected to re ect the potential importance of using Sort1 to assess the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on cancers, and particularly on colorectal cancers, most studies on the role of Sortilin/NTSR3 have been performed on in vitro models (human colorectal cancer cell lines). A recent study carried out on both cell lines and primary cultures from patients demonstrated that the overexpression of Sortilin/NTSR3 was associated with 5-fluorouracil (5-FU) resistance and a poor prognosis in colorectal cancer [ 85 ].…”
Section: Discussionmentioning
confidence: 99%